The effectiveness of the “Return to work programme” toward Social Security Organisation (SOCSO) Melaka / Norazieeyah Che Hassan - Che Hassan, Norazieeyah (Faculty of Business and Management, 2010)
This study is to determine the effectiveness of Return to Work Programme toward Social Security Organization (SOCSO) Melaka. Return to Work is a physical rehabilitation programme provided for free by SOCSO’s insured persons who suffer from disability due to injury and illness, with the aim of rehabilitating the employee’s affected limb and allowing him to return to work earlier. This study will focus to the role of Case Manager in how to implement the Return to Work Programme from the early process until the end of insured person will return to work. The case manager offers a range of occupational rehabilitation services including functional and vocational assessment, workplace assessment, job analysis, advice concerning job modification, rehabilitation counselling, advice or assistance for return-to workpants and job seeking. There are also involves several company’s practice of relating to the issue in order to determine the failure or success of Return to Work for injured worker.